The poiesis of susceptibility: Langston Hughes on queer Black friendship - Samu/elle Striewski (Currents, 2023)
The essay interprets the poem “Poem” by Langston Hughes drawing both from biographical material about the author (e.g., the biopic Looking for Langston) and from political writing about queer friendship and solidarity, notably Sara Ahmed, José Esteban Muñoz, and Judith Butler. Instead of engaging in a close reading that tries to do justice to the queerness of the “historical” Langston Hughes, the text tries to identify the power of the poem in providing suggestions of how marginalized individuals can challenge societal norms and open spaces for alternative modes of being. Referring to Michel Foucault’s ideas of gay friendship as a disruptive mode of resistance to existing structures of power, the essay develops a more nuanced idea of how Hughes’s poetry subscribes to a poiesis of susceptibility. In other words, the article argues that the poem allows for a shift away from the dominant mode of subject-formation within oppressive norms by presenting utopian speech and new modes of interrelation, namely Black, male, and queer friendship. Hence, it rethinks how those to whom the future does not belong can try to reclaim it by creating spheres where potentiality, difference, and otherness can exist and individuals can make themselves intelligible who were previously unrecognizable. Poetry functions in this process as tool that builds and reconfigures the frames of susceptibility allowing for friendships and softness that found no place before or outside of those.